2016
DOI: 10.15376/biores.12.1.270-282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Destructive Methods Based on Natural Frequency for Determining the Modulus of Elasticity of Cupressus lusitanica and Populus x canadensis

Abstract: A non-destructive method for measurement of the modulus of elasticity (MOE) was compared with the static method on beams of Cupressus lusitanica and Populus x canadensis. The dynamic method is based on the principle of the resonance frequency, using longitudinal vibrations (Timber Grader MTG, accelerometer) and the static method for measurement of the flexural modulus of elasticity is according to EN 408 (2012). The differences between the ascertained dynamic and static MOE values were 1.1% to 2.4% for the Pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
6
16
1
1
Order By: Relevance
“…Non-destructive tools were used to predict those properties through simple linear correlation analyses. The Longitudinal Vibration Method (LVM), which consists Forests 2020, 11, 418 3 of 12 of the measurement of the material's natural frequency, was used, since it was previously validated for other species, like Maritime pine [27], Poplar [28] and Blue gum [29]. The present paper intends to improve the knowledge of the Portuguese Blackwood for structural applications, highlighting the species' potential to produce glulam as a way to add value to the raw material obtained from the proliferation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Non-destructive tools were used to predict those properties through simple linear correlation analyses. The Longitudinal Vibration Method (LVM), which consists Forests 2020, 11, 418 3 of 12 of the measurement of the material's natural frequency, was used, since it was previously validated for other species, like Maritime pine [27], Poplar [28] and Blue gum [29]. The present paper intends to improve the knowledge of the Portuguese Blackwood for structural applications, highlighting the species' potential to produce glulam as a way to add value to the raw material obtained from the proliferation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Wood is a versatile material with advantages over other materials, such as concrete, steel, aluminum, and plastic. Among these advantages are the strong relationship between the mechanical strength and density, low energy consumption during production, its status as a renewable resource, and good thermal and electrical insulation (Kollmann and Côté 1968;Vidal et al 2015;Hodoušek et al 2017;Osuji and Nwankwo 2017;de Almeida et al 2018). However, wood is composed of a relatively hydrophobic matrix and hydrophilic fibers, which makes its use less disseminated because of its susceptibility to wood-deteriorating organisms (Mohan et al 2008;Temiz et al 2010;2013;Ferrarini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The present research focuses on the use of Blue gum and its combination with Poplar (both grown in Portuguese forest) for glued laminated timber. The use of non-destructive methods (longitudinal vibration method and transformed section method) was considered for the prediction of static bending properties, since previous studies have demonstrated high accuracy of both methods (Hodousek et al 2017 andMartins et al 2018). A total of 7 glulam beams were produced in laboratory, non-destructively tested through longitudinal vibration method and destructively tested following EN 408 requirements (CEN 2012).…”
Section: Introductionmentioning
confidence: 99%